Effect of pesticides on microorganisms involved in litter decomposition in cacao plantation in Ile-Ife, Nigeria - Osewole, Afolabi; Muoghalu, I.Joseph (Article in Agroforestry Systems, 2020)
Article in Agroforestry Systems,Vol. 92,No.3